Repeatability and reproducibility of ultrasonographic measurement of carotid intima thickness - Lau, Kar-Ho; Fung, Ying-Keung; Cheung, Yuk-Ting; Tsang, Wing-Keung; Ying, Michael (Journal of clinical ultrasound, 2012)
Purpose. To evaluate the repeatability and reproducibility of intima thickness (IT) measurements at different sites along the common carotid artery and compare with intima–media thickness (IMT) measurements. Methods. Ultrasound examinations of common carotid artery were performed in 30 healthy subjects and 20 patients with diabetes mellitus. Carotid IT and IMT were measured at 10 mm, 13 mm, and 16 mm upstream from the carotid bulb. Each subject was scanned by three operators to evaluate inter‐operator reproducibility. Each operator scanned the subjects twice to evaluate intra‐operator repeatability. Inter‐equipment reproducibility of the measurements was evaluated. Results. The inter‐operator reproducibility for measuring carotid IT at the three sites was 81.5%, 81.9% and 69.1%, respectively, slightly lower than carotid IMT measurement (89.7%, 86.5%, 75.2%, respectively). The intra‐operator repeatability for carotid IT measurement at the three sites ranged 76.9–89.5%, 67.4–90.3%, and 55.2–70.5%, respectively, and was lower than for IMT measurement (86.5–96.9%, 87.6–95.7%, 79.9–86.5%, respectively). The inter‐equipment reproducibility of IMT (75.7–86.6%) was slightly better than for IT measurement (71.4–75.9%). Conclusions. Ultrasonographic measurement of carotid IT is repeatable and reproducible, although not as good as IMT. Measurements preformed 10 mm to 13 mm upstream from the carotid bulb yield more repeatable and reproducible results. © 2011 Wiley Periodicals, Inc. J Clin Ultrasound 40:79–84, 2012